2003
DOI: 10.1016/s0924-9338(03)00024-5
|View full text |Cite
|
Sign up to set email alerts
|

Normal and obsessional jealousy: a study of a population of young adults

Abstract: Our study showed that 10% of a population of university students, albeit normal, have jealousy thoughts around the partner, as emerged by the specific questionnaire developed by us. This instrument permitted to clearly distinguish these subjects from patients with OCD and healthy subjects with no jealousy concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 25 publications
0
27
0
6
Order By: Relevance
“…Furthermore, it has become increasingly clear that pathological jealousy is not a unitary phenomenon, and may occur in a continuum from within a 'normal range' through to delusional jealousy (Kingham and Gordon, 2004;Mullen, 1991). Jealousy may be a burdensome manifestation of several psychopathological conditions including but not limited to affective disorders (Kingham and Gordon, 2004), obsessive-compulsive spectrum disorders (Marazziti et al, 2003a;Parker and Barrett, 1997), alcohol use disorders (DiBello et al, 2015;Michael et al, 1995), psychotic disorders (Seeman, 1979;Soyka et al, 1991;Soyka and Schmidt, 2011), and also as a neuropsychiatric disturbance in neurodegenerative diseases (e.g., Parkinson's disease) (Cipriani et al, 2012;Perugi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has become increasingly clear that pathological jealousy is not a unitary phenomenon, and may occur in a continuum from within a 'normal range' through to delusional jealousy (Kingham and Gordon, 2004;Mullen, 1991). Jealousy may be a burdensome manifestation of several psychopathological conditions including but not limited to affective disorders (Kingham and Gordon, 2004), obsessive-compulsive spectrum disorders (Marazziti et al, 2003a;Parker and Barrett, 1997), alcohol use disorders (DiBello et al, 2015;Michael et al, 1995), psychotic disorders (Seeman, 1979;Soyka et al, 1991;Soyka and Schmidt, 2011), and also as a neuropsychiatric disturbance in neurodegenerative diseases (e.g., Parkinson's disease) (Cipriani et al, 2012;Perugi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…3-Obsessive Compulsive Disorder and obsessional jealousy Compared with healthy individuals, patients with OCD are highly concerned about their partner (24). A phenomenological overlap is believed to exist between Obsessive Compulsive Disorder (OCD) and obsessional jealousy, including similarities of jealous ruminations with obsessions, unwelcome, unpleasant, repetitive, intrusive, and irrational thoughts recognized by the patient as ego dystonic (25).…”
Section: Resultsmentioning
confidence: 99%
“…Since the fear of losing the partner resulted to be a common feature of preoccupied, fearful-avoidant and dismissing individuals, although in this last case the statistical significance was not reached perhaps for the small number of subjects, it is concluded that it might represent the "organizer" of the jealousy phenomenon. In addition, as these attachment styles have been linked to the development of psychopathology [9,29,32,38,60], this might explain the vulnerability of some jealousy subjects to cross the border between normal and pathological conditions that may reach extreme levels of severity. In the light of the present findings, it would be interesting to replicate this study in individuals suffering from pathological jealousy.…”
Section: Resultsmentioning
confidence: 99%
“…The QUEGE proved to be acceptable and required 15 minutes on average to complete. In addition, it resulted to be a reliable and sensitive instrument to detect the five subtypes of jealousy in an Italian population [37][38][39].…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation